2005
DOI: 10.1016/j.ijdevneu.2005.05.008
|View full text |Cite
|
Sign up to set email alerts
|

SCL, GATA‐2 and Lmo2 expression in neurogenesis

Abstract: SCL, Lmo2 and GATA factors form common transcription complexes during hematopoietic differentiation. The overlapping expression of SCL with GATA-2 and GATA-3 in the developing brain indicated that these factors might collaborate also in the course of neural tissue differentiation. The expression pattern of Lmo2 in the developing CNS, however, is not well understood. Here, we show that neural cells in the early embryonic chick mid- and hindbrain express SCL and GATA-2, while Lmo2 is expressed only in vascular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…Our finding underlines the previously reported observation that Scl expression is restricted to postmitotic neuroprogenitor cells of the developing brain (Herberth et al, 2005;van Eekelen et al, 2003).…”
Section: ;R26rsupporting
confidence: 90%
“…Our finding underlines the previously reported observation that Scl expression is restricted to postmitotic neuroprogenitor cells of the developing brain (Herberth et al, 2005;van Eekelen et al, 2003).…”
Section: ;R26rsupporting
confidence: 90%
“…2B-D Undifferentiated NE-4C cells display many embryonic stem cell features (Oct4, Nanog) with complete inactivity of tissue-specifying bHLH (Ngn2, Mash1, Math2) or radial glia specifying (Pax6, RC2) markers [32,57,58]. Their neural commitment is indicated by the expression of Sox2 [59] and by the fact that they could develop exclusively to neural cell types [60]. The lack of Oct4 and Nanog and the presence of RGl (RC2, GLAST) immunoreactivities together with the expression of proneural bHLH (Ngn and Mash1) genes indicate that noninduced RGl cells represent a more advanced progenitor state than NE-4C cells [35].…”
Section: Resultsmentioning
confidence: 99%
“…In developing chick brain, LMO2 mRNA is limited to the vasculature, 15 although in adult mice, LMO2 mRNA expression has been demonstrated in specific portions of the thalamus and hippocampus. 16 We confirmed that in human cerebral tissue, in fetuses and adults, LMO2 protein expression is largely limited to the vasculature.…”
Section: Discussionmentioning
confidence: 99%